Illuminating black students' experiences in higher education: a critical narrative inquiry - Harrison, Shukeyla M. (My University, 2024)
White fragility has created a number of problems and challenges for Black students regarding authenticity and equality in the classroom. Racial discrimination in education and its disparities have come full circle mirroring history with the continued fight for an equitable education as a Black student. Black students continue to be mistreated and experience racial discrimination in the classroom (Witteveen & Attewell, 2022). For Black students, the effects of white fragility has had a detrimental impact on their academic success, especially on college campuses that are predominately white. Additionally, white fragility has led to disproportionate opportunities for Black students’ post-graduation (Witteveen & Attewell, 2022). Black women and men seeking employment post-graduation have a much more difficult time obtaining and retaining work because of white fragility (Witteveen & Attewell, 2022). Research literature surrounding authentic leadership theory (ALT) analyzes the “individual’s” authentic behaviors found between the subordinate and the supervisor in a work environment. My research talks about the gap in ATL that disregards authenticity in an academic environment specifically looking at the relationship between Black students and white faculty at predominately white universities. Therefore, the purpose of this study is to understand how white fragility impacts Black students and their self- authenticity in college and post-graduation. Findings from my research will provide data detailing how Black students struggle with white fragility in the classroom and that white faculty and staff are unaware of this. Findings also provide reasonable solutions for white faculty and staff to help improve and build healthy relationships with Black students in their classrooms.
Keywords: Diversity; White fragility; Leadership; Inclusion; Minorities; Communication